If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 66.6x + -6 = 18 Reorder the terms: -6 + 66.6x = 18 Solving -6 + 66.6x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 66.6x = 18 + 6 Combine like terms: -6 + 6 = 0 0 + 66.6x = 18 + 6 66.6x = 18 + 6 Combine like terms: 18 + 6 = 24 66.6x = 24 Divide each side by '66.6'. x = 0.3603603604 Simplifying x = 0.3603603604
| 6-54a^2= | | 4x^2+32x+63=0 | | 9x+12=5x-10 | | x^2-x=16 | | x^2+12x+117=0 | | -x^2+63=-2x | | -x^2=10x+9 | | -x^2-4x+77=0 | | -x^2-6x=5 | | 2x+30=14+10x | | 4x-5=13-12x | | x^2+6x+91=0 | | 2+1467(9+8)= | | 2n+3(n-1)=37 | | (3ab)(5ab)= | | 67=23x+8 | | 180-35= | | 4n+3n+5=47 | | (x+30)=(2x-5) | | y-10y=22 | | 150-.30= | | 12-7x=52-14x | | 3m=39 | | 3r=27 | | s=3g+3v | | y-3=-1(x+8) | | 15x^2-8x-18= | | 2x^2+6x-5=0 | | -6n^2+15n=0 | | 14x-9/20= | | 4x-4+10x-5= | | 12+6=8 |